A method for preparing asphalt-based composite hard carbon for sodium ion batteries

By preparing asphalt-based composite hard carbon for sodium ion batteries, using composite modifiers and mixed gas protection technology, the problems of low specific capacity and poor conductivity of asphalt-based hard carbon are solved, and the energy storage and circulation performance of the battery is significantly improved. In the application of sodium ion batteries.

CN117509608BActive Publication Date: 2024-12-20TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311521343.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2024-12-20
Estimated Expiration
2043-11-15

AI Technical Summary

Technical Problem

The existing asphalt-based hard carbon has low specific capacity and poor conductivity, which limits the energy storage performance and electron conduction speed of sodium ion batteries, and has poor structural fatigue resistance, resulting in reduced battery capacity attenuation and cycling performance.

Method used

By preparing asphalt-based composite hard carbon for sodium ion batteries, coal asphalt, composite modifier and tetrahydrofuran are used to stir and process at high temperature under specific conditions to form a composite modifier with modified resin and modified polysiloxane. Combined with the protection of mixed gases such as nitrogen and carbon dioxide, a closed-cell structure and a spherical structure are formed to improve conductivity and mechanical stability.

Benefits of technology

It significantly improves the electrochemical performance and mechanical stability of asphalt-based composite hard carbon, enhances the cycle life and high-rate performance of electrode materials, and improves the energy storage and power performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a method for preparing asphalt-based composite hard carbon for sodium ion batteries, and belongs to the technical field of asphalt-based hard carbon. The present invention is used to solve the technical problems of low specific capacity, poor electrical conductivity and poor fatigue resistance of asphalt-based hard carbon structure in the prior art. A method for preparing asphalt-based composite hard carbon for sodium ion batteries comprises the following steps: adding coal tar, composite modifier and tetrahydrofuran to a three-necked flask and stirring, raising the temperature of the three-necked flask to 45-55°C, keeping warm and stirring until the system is dissolved, and post-processing to obtain composite asphalt. The present invention is compounded by the prepared modified polysiloxane and modified resin, and the composite modifier is prepared to modify the coal tar, and the mixed gas is compounded to protect the calcination atmosphere, and the asphalt-based composite hard carbon with excellent charging specific capacity, 0.1C first charge and discharge efficiency, cycle capacity retention rate and rate performance is prepared, which is more suitable for wide application in sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of asphalt-based hard carbon processing, and in particular to a method for preparing asphalt-based composite hard carbon for sodium ion batteries. Background Art

[0002] With the rapid development of renewable energy and electric transportation, the demand for high-performance energy storage equipment is increasing. As a potential energy storage technology, sodium-ion batteries have attracted much attention due to their relatively low cost and abundant sodium resources. Battery materials with higher specific capacity, better cycle performance, and stronger rate performance are gradually being valued.

[0003] Sodium-ion batteries have many energy storage advantages, such as low cost, cycle performance temperature, low self-discharge rate, and fast charge and discharge. Among them, the performance of sodium-ion battery electrode materials has a key impact on the performance and cycle life of the battery. Asphalt is an abundant natural resource with low price and high carbon content and conductivity. Asphalt-based composite hard carbon as an electrode material shows good electrochemical performance and stability, so it has broad application prospects in the field of sodium-ion batteries.

[0004] The asphalt-based hard carbon in the prior art has low specific capacity and poor conductivity, which limits the energy storage performance and electron conduction speed of sodium ion batteries, affects the power performance and rapid charge and discharge rate of the battery, and the existing asphalt-based hard carbon structure has poor fatigue resistance. In sodium ion batteries, during charging, sodium ions will migrate from the positive electrode of the battery to the negative electrode and embed in the negative electrode material. During discharge, sodium ions will be deintercalated from the negative electrode and return to the positive electrode. When embedded in the electrode material, sodium ions will occupy the vacant positions in the atomic lattice. During the embedding / deintercalation process of sodium ions, the electrode material lattice will expand and contract, destroying the solid electrolyte interface membrane, leading to the destruction of the electrode structure, causing the battery capacity to decay and the cycle performance to decline.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing asphalt-based composite hard carbon for sodium ion batteries, which is used to solve the technical problems in the prior art that asphalt-based hard carbon has low specific capacity and poor conductivity, which limits the energy storage performance and electron conduction speed of sodium ion batteries, affects the power performance and rapid charge and discharge rate of the battery, and the asphalt-based hard carbon structure has poor fatigue resistance. During the charge and discharge process of the sodium ion battery, sodium ions are embedded / de-embedded in the electrode material, which will cause the expansion and contraction of the electrode material lattice, destroy the solid electrolyte interface film, lead to the destruction of the electrode structure, and cause the battery capacity decay and cycle performance degradation.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a pitch-based composite hard carbon for a sodium ion battery comprises the following steps:

[0009] S1. Add coal tar, composite modifier and tetrahydrofuran into a three-necked flask and stir. Raise the temperature of the three-necked flask to 45-55° C. and stir until the system is dissolved. Perform post-treatment to obtain composite asphalt.

[0010] S2. Place the composite asphalt in a tubular furnace, raise the temperature of the tubular furnace to 180-200°C under a mixed gas protection environment, keep the temperature for 3-4 hours, cool it naturally to room temperature, grind it, and pass it through a 100-mesh sieve to obtain pretreated asphalt;

[0011] S3. Add the pretreated asphalt into a tubular furnace. Under the protection of an argon gas environment, increase the temperature of the tubular furnace to 1350-1400°C at a rate of 5°C / min, keep the temperature for 120-150 minutes, cool it naturally to room temperature, grind it through a 300-mesh sieve, and obtain asphalt-based composite hard carbon.

[0012] Further, the composite modifier is processed by the following steps:

[0013] A1, adding p-hydroxybenzylamine, tetrahydrofuran and triethylamine into a three-necked flask and stirring, raising the temperature of the three-necked flask to 55-65° C., adding 30 wt % hexachlorocyclotriphosphazene / tetrahydrofuran solution dropwise into the three-necked flask, and keeping the temperature for reaction for 6-8 hours, and post-treating to obtain intermediate I;

[0014] The synthetic reaction principle of intermediate I is:

[0015]

[0016] A2, adding intermediate I, epoxy resin and tetrahydrofuran into a three-necked flask, stirring until the system is dissolved, adding a catalyst into the three-necked flask, raising the temperature of the three-necked flask to reflux the system, keeping the temperature for reaction for 6-8h, and post-treating to obtain a modified resin;

[0017] The synthetic reaction principle of modified resin is:

[0018]

[0019]

[0020]

[0021] A3. Add the modified resin, modified polysiloxane and tetrahydrofuran into a three-necked flask and stir until the system is dissolved. Stir at room temperature for 2-3 hours and post-treat to obtain a composite modifier.

[0022] Furthermore, in step A1, the molar ratio of p-hydroxybenzylamine to hexachlorocyclotriphosphazene is 6:1, the amount of tetrahydrofuran is 4 times the weight of p-hydroxybenzylamine, and the amount of triethylamine is 0.3 times the amount of tetrahydrofuran. The post-treatment operation includes: after the reaction is completed, the three-necked flask is kept at 55-65° C., tetrahydrofuran is evaporated under reduced pressure, anhydrous ethanol is added to the three-necked flask, stirred and dispersed for 30-50 minutes, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed three times with anhydrous ethanol and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60° C., and vacuum dried to constant weight to obtain intermediate I.

[0023] Furthermore, in step A2, the usage ratio of intermediate I, epoxy resin, tetrahydrofuran and catalyst is 1g:2.6g:15mL:0.2g, the epoxy resin is E-06 bisphenol A type epoxy resin, the catalyst is 5mol / L hydrochloric acid, and the post-treatment operation includes: after the reaction is completed, the three-necked flask is kept warm, after the solvent is evaporated under reduced pressure, the temperature of the three-necked flask is reduced to room temperature to obtain a modified resin.

[0024] Furthermore, in step A3, the amount ratio of the modified resin, the modified polysiloxane and tetrahydrofuran is 1g:2g:15mL, and the post-treatment operation includes: after the stirring is completed, the temperature of the three-necked flask is increased to 40-50°C, and the solvent is evaporated under reduced pressure to obtain a composite modifier.

[0025] Furthermore, the modified polysiloxane is processed by the following steps: 4,6-diamino-1,3,5-triazine-2-acetic acid is added to a nitrogen-protected three-necked flask and stirred, the temperature of the three-necked flask is lowered to 10-15°C, 3-isocyanatepropyltrimethoxysilane is slowly added to the three-necked flask, after the addition is completed, the temperature of the three-necked flask is increased to room temperature, and the reaction is kept warm for 40-60 minutes, dilute hydrochloric acid and N,N-dimethylformamide are added to the three-necked flask, the temperature of the three-necked flask is increased to 70-80°C, and the reaction is kept warm for 22-24 hours, and the modified polysiloxane is obtained by post-treatment.

[0026] The synthetic reaction principle of modified silicone resin is:

[0027]

[0028] Furthermore, the molar ratio of the 4,6-diamino-1,3,5-triazine-2-acetic acid and 3-isocyanatepropyltrimethoxysilane is 1:1; the amount ratio of the dilute hydrochloric acid, N,N-dimethylformamide and 3-isocyanatepropyltrimethoxysilane is 3mL:5mL:1g, and the concentration of the dilute hydrochloric acid is 2-4mol / L. The post-treatment operation includes: taking another three-necked flask, adding a large amount of deionized water to the three-necked flask and stirring, after the reaction is completed, slowly adding the reaction system to the three-necked flask filled with deionized water, solid precipitation, the temperature of the three-necked flask is reduced to 15-20°C, and the crystallization is kept warm for 20-30min, and the filter cake is filtered, and the filter cake is washed three times with deionized water and then transferred to a drying oven at a temperature of 80-85°C, dried to constant weight, crushed, and passed through a 100-mesh sieve to obtain a modified polysiloxane.

[0029] Furthermore, in step S1, the amount ratio of coal tar, composite modifier and tetrahydrofuran is 5g:2g:25mL, the coal tar is a high-temperature asphalt, with a softening point of 120-160°C, an ash content of less than 1%, a coking value of higher than 50%, a fixed carbon content of more than 40%, a volatile content of 50-60%, and a fineness of 0-3mm. The post-processing operation includes: after the reaction is completed, the temperature of the three-necked flask is increased to 60°C, the solvent is evaporated under reduced pressure, the reaction system is poured out of the three-necked flask while hot, and the temperature is reduced to solidify to obtain a composite asphalt; in step S2, the mixed gas is composed of carbon dioxide, oxygen and nitrogen in a volume ratio of 3:2:2.

[0030] The present invention has the following beneficial effects:

[0031] The asphalt-based composite hard carbon for sodium ion batteries of the present invention is prepared by a substitution addition reaction of hydroxybenzylamine and hexachlorocyclotriphosphazene in a molar ratio of 6:1 to prepare an intermediate I having benzylamine-modified cyclotriphosphazene, and then the intermediate I reacts with an epoxy resin under a catalyst condition to form a modified resin modified with the epoxy resin on the intermediate I; the benzylamine-modified cyclotriphosphazene may be more similar to the E-06 epoxy resin in chemical structure because they both contain similar chemical groups such as benzene rings and nitrogen atoms, thereby reducing the chemical incompatibility between different materials, and the polar groups on the modified resin, such as amino groups or hydroxyl groups, have similar polar properties to the oxygen-containing compounds or other polar components in the coal tar pitch, thereby promoting the interaction between the modified resin and the coal tar pitch and improving the compatibility between the modified resin and the coal tar pitch; the benzylamine-modified cyclotriphosphazene itself has good adhesion performance, and by modifying the epoxy resin with the benzylamine-modified cyclotriphosphazene, the adhesion properties of the modified resin are further improved, while helping to establish a stronger interface bond between the modified resin and the coal tar pitch, thereby reducing stress concentration on the interface.

[0032] The asphalt-based composite hard carbon for sodium ion batteries of the present invention, in the preparation process, the carboxyl group on 4,6-diamino-1,3,5-triazine-2-acetic acid and the isocyanate group on 3-isocyanate propyltrimethoxysilane react in a molar ratio of 1:1 under an oxygen-free environment to prepare an intermediate modified with 4,6-diamino-1,3,5-triazine; in a hydrochloric acid and DMF system, the siloxane bond on the intermediate is disconnected to form a silanol group, and a condensation reaction is carried out to generate a spatially cross-linked modified polysiloxane with a spherical structure; the 4,6-diamino-2-triazine-acetic acid modified on the surface of the modified polysiloxane is reacted with the isocyanate group on the 3-isocyanate propyltrimethoxysilane in a molar ratio of 1:1. 6-Diamino-1,3,5-triazine contains a large number of amino groups. When it is mixed with a modified resin, the alkylene oxide on the modified resin can react with the amino groups on the surface of the modified polysiloxane to graft the modified polysiloxane onto the modified resin. In addition, the modified polysiloxane has similar chemical groups to the amino groups, long branched chains, etc. modified on the modified resin, so that the modified polysiloxane can be evenly dispersed in the modified resin and establish a stable chemical connection with the modified resin, so that the modified polysiloxane can be evenly mixed with the coal tar along with the modified resin, thereby improving the dispersibility of the modified polysiloxane in the coal tar.

[0033] The asphalt-based composite hard carbon for sodium ion batteries of the present invention is prepared by dispersing coal tar and a composite modifier in a tetrahydrofuran environment, and then subjecting the composite asphalt to a high-temperature treatment under the protection of a mixed gas atmosphere consisting of carbon dioxide, oxygen and nitrogen, using nitrogen as a diluent gas to reduce the concentrations of oxygen and carbon dioxide to control the oxygen partial pressure in the atmosphere and adjust the oxygen and carbon dioxide concentrations in the atmosphere; the composite asphalt is oxidized and carbonated by the oxygen and carbon dioxide in the mixed gas, and a large number of closed-cell structures are uniformly constructed inside the hard carbon by physical activation pore formation with carbon dioxide and gas-phase carbon coating, thereby improving the electrochemical properties of the asphalt-based composite hard carbon; 4,6-diamino-1,3,5-triazine is a nitrogen-containing compound that has the property of promoting electron conduction. After being modified on the surface of polysiloxane, it can provide additional charge transfer channels and improve its conductivity; the amino functional group has nitrogen atoms that can provide lone pairs of electrons, and these lone pairs of electrons can react with alkali metal ions (such as N a+) causes charge transfer, and the amino functional group introduces additional adsorption sites, providing more places to adsorb and retain ions, increasing the adsorption sites and storage capacity of alkali metal ions on the surface of asphalt-based hard carbon materials; polysiloxane can act as a stability enhancer, increase the mechanical stability of asphalt-based composite hard carbon, and cooperate with the uniformly distributed closed-pore structure inside the hard carbon to reduce the occurrence of structural fatigue of the electrode material, and form a stable protective film on the electrode surface, thereby improving the cycle life of the electrode material; the composite modifier contains a large amount of amino and phosphorus elements. The introduction of phosphorus elements can react with some unstable chemical groups in the electrode material to form more stable compounds, thereby enhancing the electrochemical stability of the electrode material. Amino and phosphorus elements can also form a protective solid electrolyte interface film on the surface of the electrode material, slowing down structural fatigue and dissolution in the electrode material, so that the electrode material can maintain high performance in more charge and discharge cycles. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1:

[0035] The method for preparing a pitch-based composite hard carbon for a sodium ion battery of this embodiment comprises the following steps:

[0036] S1. Preparation of modified polysiloxane

[0037] Weigh: 50.0 g of 4,6-diamino-1,3,5-triazine-2-acetic acid was added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask was lowered to 10°C. 60.7 g of 3-isocyanatepropyltrimethoxysilane was slowly added dropwise to the three-necked flask. After the addition was completed, the temperature of the three-necked flask was raised to room temperature and kept warm for 40 minutes. 182.1 mL of 2 mol / L hydrochloric acid and 303.5 mL of N,N-dimethylformamide were added to the three-necked flask. The temperature of the three-necked flask was raised to 70°C and kept warm for 22 hours.

[0038] Take another three-necked flask, add 1500mL of deionized water into the three-necked flask and stir. After the reaction is completed, slowly add the reaction system into the three-necked flask filled with deionized water. Solid precipitates. The temperature of the three-necked flask is lowered to 15°C, and the crystallization is kept warm for 20 minutes. Filter, wash the filter cake three times with deionized water, and then transfer it to a drying oven at a temperature of 80°C, dry it to constant weight, crush it, and pass it through a 100-mesh sieve to obtain modified polysiloxane.

[0039] S2. Preparation of modified resin

[0040] Weigh: 84.96 g of p-hydroxybenzylamine, 399.84 g of tetrahydrofuran, and 102.0 g of triethylamine, add them to a three-necked flask and stir, raise the temperature of the three-necked flask to 55° C., add 133.3 g of a 30 wt% hexachlorocyclotriphosphazene / tetrahydrofuran solution to the three-necked flask, and after the addition is complete, keep the temperature for 6 h. Keep the three-necked flask at 55° C., remove tetrahydrofuran under reduced pressure, add 500 mL of anhydrous ethanol to the three-necked flask, stir and disperse for 30 min, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then drain, transfer the filter cake to a drying oven at 50° C., and vacuum dry to constant weight to obtain intermediate I;

[0041] Weigh: 50 g of intermediate I, 125 g of epoxy resin and 750 mL of tetrahydrofuran are added to a three-necked flask, and stirred until the system is dissolved. 10 g of 5 mol / L hydrochloric acid is added to the three-necked flask, and the temperature of the three-necked flask is increased to reflux the system, and the reaction is kept warm for 6 hours. The three-necked flask is kept warm, and the solvent is evaporated under reduced pressure. The temperature of the three-necked flask is lowered to room temperature to obtain a modified resin, wherein the epoxy resin is E-06 bisphenol A type epoxy resin, and the manufacturer is: Wuhan Prov Biotechnology Co., Ltd.

[0042] S3. Preparation of composite modifier

[0043] Weigh: 30 g of modified resin, 60 g of modified polysiloxane and 450 mL of tetrahydrofuran, add into a three-necked flask and stir until the system is dissolved. Stir at room temperature for 2 h. Raise the temperature of the three-necked flask to 40° C. and evaporate the solvent under reduced pressure to obtain a composite modifier.

[0044] S4. Preparation of composite asphalt

[0045] Weigh: 100g of coal tar pitch, 40g of composite modifier and 500mL of tetrahydrofuran, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 45°C, keep warm and stir until the system is dissolved, raise the temperature of the three-necked flask to 60°C, evaporate the solvent under reduced pressure, pour the reaction system from the three-necked flask while hot, cool and solidify to obtain composite asphalt, wherein the coal tar pitch is the high-temperature asphalt part, the softening point is 120-160°C, the ash content is less than 1%, the coking value is higher than 50%, the fixed carbon is greater than 40%, the volatile matter is 50-60%, and the fineness is 0-3mm.

[0046] S4. Composite asphalt pretreatment

[0047] Mix carbon dioxide, oxygen and nitrogen in a volume ratio of 3:2:2 to form a mixed gas;

[0048] The composite asphalt was placed in a tubular furnace. Under a mixed gas protection environment, the temperature of the tubular furnace was raised to 180°C, and the mixture was kept warm for 3 hours. The mixture was naturally cooled to room temperature, ground, and passed through a 100-mesh sieve to obtain pretreated asphalt.

[0049] S5. Preparation of asphalt-based composite hard carbon

[0050] The pretreated asphalt was added into a tubular furnace. Under the protection of an argon gas environment, the temperature of the tubular furnace was increased to 1350°C at a rate of 5°C / min, and the mixture was kept warm for 120 minutes. The mixture was naturally cooled to room temperature and ground through a 300-mesh sieve to obtain asphalt-based composite hard carbon. Embodiment 2:

[0051] The method for preparing a pitch-based composite hard carbon for a sodium ion battery of this embodiment comprises the following steps:

[0052] S1. Preparation of modified polysiloxane

[0053] Weigh: 50.0 g of 4,6-diamino-1,3,5-triazine-2-acetic acid was added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask was lowered to 13°C. 60.7 g of 3-isocyanatepropyltrimethoxysilane was slowly added dropwise to the three-necked flask. After the addition was completed, the temperature of the three-necked flask was raised to room temperature and kept warm for 50 minutes. 182.1 mL of 3 mol / L hydrochloric acid and 303.5 mL of N,N-dimethylformamide were added to the three-necked flask. The temperature of the three-necked flask was raised to 75°C and kept warm for 23 hours.

[0054] Take another three-necked flask, add 1500mL of deionized water into the three-necked flask and stir. After the reaction is completed, slowly add the reaction system into the three-necked flask filled with deionized water. Solid precipitates. The temperature of the three-necked flask is lowered to 18°C, and the crystallization is kept warm for 25 minutes. Filter, wash the filter cake three times with deionized water, and then transfer it to a drying oven at a temperature of 83°C, dry it to constant weight, crush it, and pass it through a 100-mesh sieve to obtain modified polysiloxane.

[0055] S2. Preparation of modified resin

[0056] Weigh: 84.96 g of p-hydroxybenzylamine, 399.84 g of tetrahydrofuran, and 102.0 g of triethylamine, add them to a three-necked flask and stir, raise the temperature of the three-necked flask to 60° C., add 133.3 g of a 30 wt% hexachlorocyclotriphosphazene / tetrahydrofuran solution to the three-necked flask, and after the addition is complete, keep the temperature for 7 h. Keep the three-necked flask at 60° C., evaporate tetrahydrofuran under reduced pressure, add 500 mL of anhydrous ethanol to the three-necked flask, stir and disperse for 40 min, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then drain, transfer the filter cake to a drying oven at 55° C., and vacuum dry to constant weight to obtain intermediate I;

[0057] Weigh: 50 g of intermediate I, 125 g of epoxy resin and 750 mL of tetrahydrofuran are added to a three-necked flask, and stirred until the system is dissolved. 10 g of 5 mol / L hydrochloric acid is added to the three-necked flask, and the temperature of the three-necked flask is increased to reflux the system, and the reaction is kept warm for 7 hours. The three-necked flask is kept warm, and the solvent is evaporated under reduced pressure. The temperature of the three-necked flask is lowered to room temperature to obtain a modified resin, wherein the epoxy resin is E-06 bisphenol A type epoxy resin, and the manufacturer is: Wuhan Prov Biotechnology Co., Ltd.

[0058] S3. Preparation of composite modifier

[0059] Weigh: 30 g of modified resin, 60 g of modified polysiloxane and 450 mL of tetrahydrofuran, add into a three-necked flask and stir until the system is dissolved. Stir at room temperature for 2.5 h. Raise the temperature of the three-necked flask to 45° C. and evaporate the solvent under reduced pressure to obtain a composite modifier.

[0060] S4. Preparation of composite asphalt

[0061] Weigh: 100 g of coal tar, 40 g of composite modifier and 500 mL of tetrahydrofuran, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 50°C, keep warm and stir until the system is dissolved, raise the temperature of the three-necked flask to 60°C, evaporate the solvent under reduced pressure, pour the reaction system from the three-necked flask while hot, cool and solidify to obtain composite asphalt, wherein the coal tar is the high-temperature asphalt part, the softening point is 120-160°C, the ash content is less than 1%, the coking value is higher than 50%, the fixed carbon is greater than 40%, the volatile matter is 50-60%, and the fineness is 0-3mm.

[0062] S4. Composite asphalt pretreatment

[0063] Mix carbon dioxide, oxygen and nitrogen in a volume ratio of 3:2:2 to form a mixed gas;

[0064] The composite asphalt was placed in a tubular furnace. Under a mixed gas protection environment, the temperature of the tubular furnace was raised to 190°C, and the mixture was kept warm for 3.5 hours. The mixture was naturally cooled to room temperature, ground, and passed through a 100-mesh sieve to obtain pretreated asphalt.

[0065] S5. Preparation of asphalt-based composite hard carbon

[0066] The pretreated asphalt was added into a tubular furnace. Under the protection of an argon gas environment, the temperature of the tubular furnace was increased to 1375°C at a rate of 5°C / min, and the mixture was kept warm for 135 minutes. The mixture was naturally cooled to room temperature and ground through a 300-mesh sieve to obtain asphalt-based composite hard carbon. Embodiment three:

[0067] The method for preparing a pitch-based composite hard carbon for a sodium ion battery of this embodiment comprises the following steps:

[0068] S1. Preparation of modified polysiloxane

[0069] Weigh: 50.0 g of 4,6-diamino-1,3,5-triazine-2-acetic acid was added to a three-necked flask protected by nitrogen and stirred. The temperature of the three-necked flask was lowered to 15°C. 60.7 g of 3-isocyanatepropyltrimethoxysilane was slowly added dropwise to the three-necked flask. After the addition was completed, the temperature of the three-necked flask was raised to room temperature and kept warm for 60 minutes. 182.1 mL of 4 mol / L hydrochloric acid and 303.5 mL of N,N-dimethylformamide were added to the three-necked flask. The temperature of the three-necked flask was raised to 80°C and kept warm for 24 hours.

[0070] Take another three-necked flask, add 1500mL of deionized water into the three-necked flask and stir. After the reaction is completed, slowly add the reaction system into the three-necked flask filled with deionized water. Solid precipitates. The temperature of the three-necked flask is lowered to 20°C, and the crystallization is kept warm for 30 minutes. Filter, wash the filter cake three times with deionized water, and then transfer it to a drying oven at a temperature of 85°C, dry it to constant weight, crush it, and pass it through a 100-mesh sieve to obtain modified polysiloxane.

[0071] S2. Preparation of modified resin

[0072] Weigh: 84.96 g of p-hydroxybenzylamine, 399.84 g of tetrahydrofuran, and 102.0 g of triethylamine, add them to a three-necked flask and stir, raise the temperature of the three-necked flask to 65° C., add 133.3 g of a 30 wt% hexachlorocyclotriphosphazene / tetrahydrofuran solution to the three-necked flask, and after the addition is complete, keep the mixture warm for 8 h. Keep the three-necked flask warm at 65° C., remove tetrahydrofuran under reduced pressure, add 500 mL of anhydrous ethanol to the three-necked flask, stir and disperse for 50 min, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake three times with anhydrous ethanol, and then drain, transfer the filter cake to a drying oven at 60° C., and vacuum dry to constant weight to obtain intermediate I;

[0073] Weigh: 50 g of intermediate I, 125 g of epoxy resin and 750 mL of tetrahydrofuran are added to a three-necked flask, and stirred until the system is dissolved. 10 g of 5 mol / L hydrochloric acid is added to the three-necked flask, and the temperature of the three-necked flask is increased to reflux the system, and the reaction is kept warm for 8 hours. The three-necked flask is kept warm, and the solvent is evaporated under reduced pressure. The temperature of the three-necked flask is lowered to room temperature to obtain a modified resin, wherein the epoxy resin is E-06 bisphenol A type epoxy resin, and the manufacturer is: Wuhan Proloff Biotechnology Co., Ltd.

[0074] S3. Preparation of composite modifier

[0075] Weigh: 30 g of modified resin, 60 g of modified polysiloxane and 450 mL of tetrahydrofuran, add into a three-necked flask and stir until the system is dissolved. Stir at room temperature for 3 h. Raise the temperature of the three-necked flask to 50° C. and evaporate the solvent under reduced pressure to obtain a composite modifier.

[0076] S4. Preparation of composite asphalt

[0077] Weigh: 100g of coal tar pitch, 40g of composite modifier and 500mL of tetrahydrofuran, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 55°C, keep warm and stir until the system is dissolved, raise the temperature of the three-necked flask to 60°C, evaporate the solvent under reduced pressure, pour the reaction system from the three-necked flask while hot, cool and solidify to obtain composite asphalt, wherein the coal tar pitch is the high-temperature asphalt part, the softening point is 120-160°C, the ash content is less than 1%, the coking value is higher than 50%, the fixed carbon is greater than 40%, the volatile matter is 50-60%, and the fineness is 0-3mm.

[0078] S4. Composite asphalt pretreatment

[0079] Mix carbon dioxide, oxygen and nitrogen in a volume ratio of 3:2:2 to form a mixed gas;

[0080] The composite asphalt was placed in a tubular furnace. Under a mixed gas protection environment, the temperature of the tubular furnace was raised to 200°C, and the mixture was kept warm for 4 hours. The mixture was naturally cooled to room temperature, ground, and passed through a 100-mesh sieve to obtain pretreated asphalt.

[0081] S5. Preparation of asphalt-based composite hard carbon

[0082] The pretreated asphalt was added into a tubular furnace. Under the protection of an argon gas environment, the temperature of the tubular furnace was increased to 1400°C at a rate of 5°C / min, and the mixture was kept warm for 150 minutes. The mixture was naturally cooled to room temperature and ground through a 300-mesh sieve to obtain asphalt-based composite hard carbon.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 3 is that step S1 and step S3 are eliminated, and the composite modifier in step S4 is replaced by an equal amount of modified resin.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 3 is that step S2 is eliminated and the modified resin in step S3 is replaced by an equal amount of epoxy resin.

[0087] Comparative Example 3

[0088] The difference between this comparative example and Example 3 is that the mixed gas in step S4 is replaced by an equal amount of nitrogen.

[0089] Performance Testing:

[0090] The asphalt-based composite hard carbon prepared in Example 1-3 and Comparative Example 1-3 was used as a raw material, and it was mixed and ground with the conductive agent acetylene black and the binder polyvinylidene fluoride in a weight ratio of 8:1:1. The viscosity of the entire slurry was adjusted by controlling the amount of dispersant N-methylpyrrolidone (NMP) to obtain a fine, uniform, and non-granular electrode slurry. The slurry was coated on the current collector (copper foil) using a scraper tool. The copper foil was placed in a vacuum drying oven, the temperature was set to 60°C, and the drying time was 12 hours. A disc electrode with a diameter of 10 mm was cut out using a cutting machine, and the electrode electrode was fully compacted using a tablet press to prepare an electrode sheet sample. Referring to the standard SJ / T 11793-2022 "Test Method for Electrochemical Performance of Lithium-ion Battery Electrode Materials" tests the 0.1C charging specific capacity, 0.1C first charge and discharge efficiency, 100th cycle capacity retention rate at 0.5C rate, and 5C high rate performance of the electrode sample. The specific test results are shown in the table below:

[0091] Group Project <![CDATA[0.1C charge specific capacity / mAh·g -1 > 0.1C first charge and discharge efficiency / % Cycle capacity retention rate / % High rate performance / % Example 1 563.5 95.5 96.3 91.4 Example 2 558.9 94.8 95.4 90.8 Example 3 561.2 95.2 95.9 91.3 Comparative Example 1 486.7 86.8 85.2 81.1 Comparative Example 2 488.5 88.6 89.3 84.2 Comparative Example 3 492.3 93.1 92.6 87.3

[0092] Data Analysis:

[0093] Comparative analysis of the data in the above table shows that the 0.1C charge capacity of the pitch-based composite hard carbon prepared by Examples 1-3 of the present invention reaches 561.2 mAh·g -1 The 0.1C first charge and discharge efficiency reaches 95.2%, the cycle capacity retention rate after 100 cycles at 0.5C rate reaches 95.9%, and the 5C high rate performance reaches 91.2%. All the test data are better than the comparative example, indicating that the asphalt-based composite hard carbon prepared by the present invention is modified by modifying the coal tar by composite modifier prepared by modifying polysiloxane and modified resin, and the mixed gas is compounded to protect the calcination atmosphere, so as to prepare an asphalt-based composite hard carbon with excellent charging specific capacity, 0.1C first charge and discharge efficiency, cycle capacity retention rate and rate performance, and is more suitable for wide application in sodium ion batteries.

[0094] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0095] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0096] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a pitch-based composite hard carbon for a sodium ion battery, characterized in that: The following steps are involved: S1. Add coal tar, composite modifier and tetrahydrofuran into a three-necked flask and stir. Raise the temperature of the three-necked flask to 45-55° C. and stir until the system is dissolved. Perform post-treatment to obtain composite asphalt. S2. Place the composite asphalt in a tubular furnace, raise the temperature of the tubular furnace to 180-200°C under a mixed gas protection environment, keep the temperature for 3-4 hours, cool it naturally to room temperature, grind it, and pass it through a 100-mesh sieve to obtain pretreated asphalt; S3, adding the pretreated asphalt into a tubular furnace, under the protection of argon gas environment, raising the temperature of the tubular furnace to 1350-1400°C at a rate of 5°C / min, keeping the temperature for 120-150min, cooling naturally to room temperature, grinding through a 300-mesh sieve, and obtaining asphalt-based composite hard carbon; The composite modifier is processed by the following steps: A1, adding p-hydroxybenzylamine, tetrahydrofuran and triethylamine into a three-necked flask and stirring, raising the temperature of the three-necked flask to 55-65° C., adding 30 wt % hexachlorocyclotriphosphazene / tetrahydrofuran solution dropwise into the three-necked flask, and keeping the temperature for reaction for 6-8 hours, and post-treating to obtain intermediate I; A2, adding intermediate I, epoxy resin and tetrahydrofuran into a three-necked flask, stirring until the system is dissolved, adding a catalyst into the three-necked flask, raising the temperature of the three-necked flask to reflux the system, keeping the temperature for reaction for 6-8h, and post-treating to obtain a modified resin; A3. Add the modified resin, modified polysiloxane and tetrahydrofuran into a three-necked flask and stir until the system is dissolved. Stir at room temperature for 2-3 hours and post-treat to obtain a composite modifier.

2. The method for preparing a pitch-based composite hard carbon for sodium ion battery according to claim 1, characterized in that: In step A1, the molar ratio of p-hydroxybenzylamine to hexachlorocyclotriphosphazene is 6:1, the amount of tetrahydrofuran used is 4 times the weight of p-hydroxybenzylamine, and the amount of triethylamine used is 0.3 times the amount of tetrahydrofuran used. The post-treatment operation in step A1 includes: after the reaction is completed, the three-necked flask is kept at 55-65° C., tetrahydrofuran is evaporated under reduced pressure, anhydrous ethanol is added to the three-necked flask, stirred and dispersed for 30-50 minutes, the temperature of the three-necked flask is lowered to room temperature, suction filtered, the filter cake is washed three times with anhydrous ethanol and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60° C., and vacuum dried to constant weight to obtain intermediate I.

3. The method for preparing a pitch-based composite hard carbon for sodium ion battery according to claim 1, characterized in that: In step A2, the usage ratio of intermediate I, epoxy resin, tetrahydrofuran and catalyst is 1g:2.6g:15mL:0.2g, the epoxy resin is E-06 bisphenol A type epoxy resin, the catalyst is 5mol / L hydrochloric acid, and the post-processing operation in step A2 includes: after the reaction is completed, the three-necked flask is kept warm, and after the solvent is evaporated under reduced pressure, the temperature of the three-necked flask is reduced to room temperature to obtain a modified resin.

4. The method for preparing a pitch-based composite hard carbon for sodium ion battery according to claim 1, characterized in that: In step A3, the amount ratio of the modified resin, the modified polysiloxane and tetrahydrofuran is 1g:2g:15mL. The post-treatment operation in step A3 includes: after the stirring is completed, the temperature of the three-necked flask is increased to 40-50°C, and the solvent is evaporated under reduced pressure to obtain a composite modifier.

5. The method for preparing a pitch-based composite hard carbon for sodium ion battery according to claim 1, characterized in that: The modified polysiloxane is processed by the following steps: adding 4,6-diamino-1,3,5-triazine-2-acetic acid into a three-necked flask protected by nitrogen and stirring, lowering the temperature of the three-necked flask to 10-15°C, slowly dropping 3-isocyanate propyltrimethoxysilane into the three-necked flask, and after the dropping is completed, raising the temperature of the three-necked flask to room temperature, keeping the temperature for reaction for 40-60 minutes, adding dilute hydrochloric acid and N,N-dimethylformamide into the three-necked flask, raising the temperature of the three-necked flask to 70-80°C, keeping the temperature for reaction for 22-24 hours, and post-treating to obtain the modified polysiloxane.

6. The method for preparing a pitch-based composite hard carbon for sodium ion battery according to claim 5, characterized in that: The molar ratio of the 4,6-diamino-1,3,5-triazine-2-acetic acid and 3-isocyanate propyl trimethoxy silane is 1:1; the amount ratio of the dilute hydrochloric acid, N,N-dimethylformamide and 3-isocyanate propyl trimethoxy silane is 3mL:5mL:1g, and the concentration of the dilute hydrochloric acid is 2-4mol / L. The post-treatment operation in the preparation process of the modified polysiloxane includes: taking another three-necked flask, adding a large amount of deionized water to the three-necked flask and stirring, after the reaction is completed, slowly adding the reaction system to the three-necked flask filled with deionized water, solid precipitation, the temperature of the three-necked flask is reduced to 15-20°C, and the crystallization is kept warm for 20-30min, and the filter cake is filtered, and the filter cake is washed three times with deionized water and then transferred to a drying oven at a temperature of 80-85°C, dried to constant weight, crushed, and passed through a 100-mesh sieve to obtain the modified polysiloxane.

7. The method for preparing a pitch-based composite hard carbon for sodium ion battery according to claim 1, characterized in that: In step S1, the amount ratio of coal tar, composite modifier and tetrahydrofuran is 5g:2g:25mL, the coal tar is a high-temperature asphalt, with a softening point of 120-160°C, an ash content of less than 1%, a coking value of more than 50%, a fixed carbon content of more than 40%, a volatile content of 50-60%, and a fineness of 0-3mm. The post-processing operation in step S1 includes: after the reaction is completed, the temperature of the three-necked flask is increased to 60°C, the solvent is evaporated under reduced pressure, the reaction system is poured out of the three-necked flask while hot, and the temperature is reduced to solidify to obtain a composite asphalt; in step S2, the mixed gas is composed of carbon dioxide, oxygen and nitrogen in a volume ratio of 3:2:2.